English literature of the 1920s - Ayers, David, 1960- (Edinburgh University Press, 1999)
Focusing principally on the novel, this book treats works that are regarded as modernist alongside non-modernist and popular forms. These texts are examined within the context of social concerns, including gender, class politics, and the empire.